Serological and molecular characterization of pathogenic Leptospira among small mammals from Selangor wet markets, Malaysia - Bahtiar Affendy, Norliza (2020)
In Malaysia, high number of leptospirosis cases observed in urban areas was concentrated with rat populations. The increasing trend of leptospirosis cases and death reports has called for an urgent need to study the Leptospira species in the animals. Thus, this study was conducted to investigate the serological and molecular epidemiology of Leptospira among small mammals in Selangor wet markets from December 2016 to February 2018. The serum of the captured animals was collected for the detection of leptospiral antibodies via Microscopic Agglutination Test (MAT). The rodent’s kidneys were also harvested and subjected to Leptospira isolation by culture method and polymerase chain reaction (PCR) using flaB genes. Then, all positives samples were subjected to multi-locus sequence typing (MLST) Scheme 1 for genotypic characterization. A total of 89 small mammals captured were identified as: Rattus norvegicus (53.9%), Rattus rattus (23.6%) and Suncus murinus (22.5%). From 89 serum samples, 19.1% showed presence of leptospiral antibodies and reacted to three serovars; serovar Bataviae (n=14; 15.7%), serovar Javanica (n=2; 2.2%) and serovar Patoc (n=1; 1.1%) Whereas, for 89 culture samples, 16.9% (n=15) showed positive growth of spirochetes in which all of them were positive for pathogenic Leptospira via PCR of flaB gene. Polymerase chain reaction of 89 kidney samples showed 31.5% (n=28) positive for flaB gene. The phylogenetic analysis of flaB gene on 31 samples (15 culture isolates and 16 kidney samples without duplicate sample source) revealed 2 clusters of species with L. interrogans (n=28; 90.3%) being the predominant species and L. borgpetersenii (n=3; 9.7%). Genotyping by MLST was successfully performed on 27 samples and three clones namely L. interrogans serovar Bataviae ST 50 (n=19), L. interrogans ST205 (n=7) and L. borgpetersenii serovar Javanica ST 143 (n=1) were identified. In conclusion, a high detection rate of pathogenic Leptospira and its antibody in small mammals indicates wet market may pose a risk in spreading leptospirosis. The identified serovars in animals are also the common serovar found in infected human, indicating the inter-relationship of carriage and host to cause the disease.